2019
DOI: 10.4103/jfmpc.jfmpc_204_19
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of Interleukin (IL)-1β, IL-6, tumor necrosis factor-α, epidermal growth factor, and β2-microglobulin levels in gingival crevicular fluid during human Orthodontic tooth movement (OTM)

Abstract: Aim: The aim of this study was to identify and quantify the various cytokines in human gingival crevicular fluid (GCF), and to investigate the changes in their levels during orthodontic tooth movement (OTM). Materials and Methods: A statistically significant no. of subjects (n = 10 and mean age = 15.6 years) were included in the study. A maxillary cuspid of each subject having one treatment for distal orthodontic tooth movement served as the experimental tooth, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Several reports showed that the compression force in orthodontic tooth movement (OTM) in mice induces the expression of TNF-α [75][76][77][78][79][80]. Our studies found that TNF-α plays an essential role in OTM in both TNFR1-and TNFR2-deficient mice, which experienced less tooth movement distance compared to wild-type mice [81][82][83][84][85][86].…”
Section: Tnfr1 and Tnfr2 In Osteoclasts And The Role Of The Interacti...mentioning
confidence: 47%
“…Several reports showed that the compression force in orthodontic tooth movement (OTM) in mice induces the expression of TNF-α [75][76][77][78][79][80]. Our studies found that TNF-α plays an essential role in OTM in both TNFR1-and TNFR2-deficient mice, which experienced less tooth movement distance compared to wild-type mice [81][82][83][84][85][86].…”
Section: Tnfr1 and Tnfr2 In Osteoclasts And The Role Of The Interacti...mentioning
confidence: 47%
“…In addition, TNF-α is expressed in the PDL and alveolar bone during orthodontic tooth movement [ 64 , 65 ]. Moreover, in GCF studies during OTM, many reports have shown that PGE, IL-1, IL-6, IL-17, and TNF-α can be detected in compression and/or tension side [ 66 , 67 , 68 , 69 ]. Therefore, these inflammatory cytokines intricately intertwined with one another during OTM, and play important roles in bone remodeling.…”
Section: Inflammatory Mediators In Orthodontic Tooth Movementmentioning
confidence: 99%
“…According to the previous results, IL-1 and TNF-α concentrations reach a maximum value in the initial 24-hour time interval [23]. Other authors also report a similar increase in TNFα in the initial 24-hour time interval vs. baseline [24,25]. It was also revealed that concentration of TNF-α in force area was higher than the control side [26].…”
Section: Discussionmentioning
confidence: 56%